WHY DOES HERITAGE MATTER: AN ANSWER TO READING LEGACIES. - Tucker, Aviezer (Porównania, 2019)
If the legacies of totalitarianism are significant for understanding the present, the global emergence of populism in post-totalitarian, post-authoritarian, and post-liberal societies since 2010 is puzzling. It seems to support some version of economic determinism rather than historical path dependency. I argue that the universal common denominator is blocked social mobility. The elites that protect them selves by blocking mobility and their social and political contexts are local. 1989 was a political, not a social revolution. The continuous late Communist elite transmuted political into economic capital and prevented the establishment of the rule of law. When economies and mobility expanded, the effects of the late totalitarian continuity laid dormant, the recession awoke them.